2003
DOI: 10.1029/2000jc000327
|View full text |Cite
|
Sign up to set email alerts
|

Organic‐rich sediments in ventilated deep‐sea environments: Relationship to climate, sea level, and trophic changes

Abstract: [1] Sediments on the Namibian Margin in the SE Atlantic between water depths of $1000 and $3600 m are highly enriched in hydrocarbon-prone organic matter. Such sedimentation has occurred for more than 2 million years and is geographically distributed over hundreds of kilometers along the margin, so that the sediments of this region contain a huge concentrated stock of organic carbon. It is shown here that most of the variability in organic content is due to relative dilution by buried carbonates. This reflects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
2
17
0
2
Order By: Relevance
“…S2 in the Supplement). The MIS 5 pollen concentrations were comparable to those found in other oceanic margins (Sánchez Goñi et al, 1999), even though BUS facilitates preservation of pollen grains and other organic microfossils at this site (Bertrand et al, 2003). The low net primary productivity that characterises the vegetation of southwestern Africa (Imhoff et al, 2004) is probably linked to low pollen production and could explain relatively low pollen concentrations in the continental margin (Fig.…”
Section: Pollen Preservation and Sources In Marine Core Md96-2098mentioning
confidence: 53%
See 1 more Smart Citation
“…S2 in the Supplement). The MIS 5 pollen concentrations were comparable to those found in other oceanic margins (Sánchez Goñi et al, 1999), even though BUS facilitates preservation of pollen grains and other organic microfossils at this site (Bertrand et al, 2003). The low net primary productivity that characterises the vegetation of southwestern Africa (Imhoff et al, 2004) is probably linked to low pollen production and could explain relatively low pollen concentrations in the continental margin (Fig.…”
Section: Pollen Preservation and Sources In Marine Core Md96-2098mentioning
confidence: 53%
“…The water exchange between the two oceans is termed the Agulhas leakage and is suggested as a potential trigger of meridional overturning circulation changes (Beal et al, 2011;Biastoch et al, 2008). The Benguela Upwelling System (BUS) also affects climate in southwestern Africa and is linked to arid conditions on the continent (Lutjeharms and Meeuwis, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen isotopic composition shows a weak negative correlation with the TOC records. By virtue of this inverse relationship, Bertrand et al [2003] interpreted the δ 15 N signal of MD962086 as representing past surface nitrate utilization, lower values indicating lower nitrate utilization by primary producers during periods of high rate of nutrient supply and associated productivity. The same interpretation was put forward by Holmes et al [1999, 2002, 2003] both in the modern Benguela and ancient Angola systems.…”
Section: Upwelling Dynamics and Nitrate Cycling In The Pastmentioning
confidence: 99%
“…However, at least two other factors should be considered: (i) the presence of well preserved labile material (of marine and/or terrestrial origin) which adds its own signature to that of the refractory constituents; e.g. for the marine material this is supported by recent work which clearly demonstrated that algal material can be preserved after settling to great depth in well-oxygenated waters (Bertrand et al, 2003;Pichevin et al, 2004); (ii) the exact nature of the terrestrial input, whose composition and quality can which differ greatly whether it is inherited from soils (and thus is mostly made up of residual humic substances) or whether it is mostly made up of woody debris (rich in cellulose and lignin) or of leaves (rich in waxy components). In an attempt at overcoming these various difficulties, we suggest interpreting the n-alkane/n-alkene distributions, obtained from kerogen pyrolysis, in the same way as is classically done for the free hydrocarbon distributions where it has been assumed for a long-time that the low and high molecular weight ends derive from marine and terrestrial contributions, respectively.…”
Section: Om Type and Originmentioning
confidence: 86%